COLLABORATIVE LEARNING UNTUK MENINGKATKAN PEMAHAMAN KETRAMPILAN DAN MINAT BELAJAR SISWA DALAM MELAKUKAN INSTALASI SISTEM OPERASI DASAR DI KELAS X TKJ 1 SMK NEGERI 1 LUMAJANG - RT. Surian Baroto (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2015)
The objective of this study is to develop an innovative instructional strategy through the implementation of collaborative learning to develop the students’ understanding and learning motivationon the subject of the installation of basic operating system (SOD). In this study, the researcher employed classroom action research (CAR) as the research design in which the researcher carries out the cyclical procedure of the study: planning, implementing, observing, and reflecting on the action.This study was carried out in three cycles. The subject of this study is the students of class X TKJ 1, SMK Negeri 1 Lumajang, in the academic year 2013/2014. Test and observation used as the data collection methods in this study. On the basis of research findings, it can be concluded that collaborative learning strategy could be able to improve the students’ activity in the productive subject of TKJ. In addition, the study could be able to improve the students’ academic achievement.Keywords: Collaborative learning, academic achievement.